Flexible solar and thermal energy conversion devices: Organic photovoltaics (OPVs), organic thermoelectric generators (OTEGs) and hybrid PV-TEG systems. (December 2022) - Sharma, Anirudh; Masoumi, Saeed; Gedefaw, Desta; O'Shaughnessy, Seamus; Baran, Derya; Pakdel, Amir
Highlights: State-of-the-art organic semiconducting materials and their challenges for photovoltaic and thermoelectric applications are reviewed. Effective strategies for improving the performance of organic photovoltaic and organic thermoelectric materials are discussed. Flexible OPVs and OTEGs, their fabrication technique, and their potentials and challenges are presented. PV-TEG hybrid systems, their advantageous over single PV and TEG units, and practical solutions to address current challenges are explained. Abstract: Solar and thermal energy conversion are two major renewable energy technologies highly sought after in the past two decades by academia, industry, and policymakers. Besides the traditionally large-size solar and thermal energy convertors, more recently, lightweight, flexible solar cells and thermoelectric generators (TEGs) based on organic semiconductor materials have attracted much attention due to the booming development of wearable electronics. In this article, we comprehensively review the scientific advances in the field of organic photovoltaics and organic thermoelectric materials and devices, focusing both on the fundamental processes as well as the development of flexible devices. This review brings together state-of-the-art technological advancements in the field of hybrid photovoltaic-thermoelectric energy harvesters, with overarching relevance and implications for the development of self-powered wearable electronics for internet-of-things (IoT) applications. Graphical abstract: Image, graphical abstract